Developing a new stream metric for comparing stream function using a bank–floodplain sediment budget: a case study of three Piedmont streams. Issue 8 (23rd September 2012) - Schenk, Edward R.; Hupp, Cliff R.; Gellis, Allen; Noe, Greg
ABSTRACT: A bank and floodplain sediment budget was created for three Piedmont streams tributary to the Chesapeake Bay. The watersheds of each stream varied in land use from urban (Difficult Run) to urbanizing (Little Conestoga Creek) to agricultural (Linganore Creek). The purpose of the study was to determine the relation between geomorphic parameters and sediment dynamics and to develop a floodplain trapping metric for comparing streams with variable characteristics. Net site sediment budgets were best explained by gradient at Difficult Run, floodplain width at Little Conestoga Creek, and the relation of channel cross‐sectional area to floodplain width at Linganore Creek. A correlation for all streams indicated that net site sediment budget was best explained by relative floodplain width (ratio of channel width to floodplain width). A new geomorphic metric, the floodplain trapping factor, was used to compare sediment budgets between streams with differing suspended sediment yields. Site sediment budgets were normalized by floodplain area and divided by the stream's sediment yield to provide a unitless measure of floodplain sediment trapping. A floodplain trapping factor represents the amount of upland sediment that a particular floodplain site can trap (e.g. a factor of 5 would indicate that a particular floodplain site traps the equivalent of 5 times that area in upland erosional source area). Using this factor we determined that Linganore Creek had the highest gross and net (floodplain deposition minus bank erosion) floodplain trapping factor (107 and 46, respectively) that Difficult Run the lowest gross floodplain trapping factor (29) and Little Conestoga Creek had the lowest net floodplain trapping factor (–14, indicating that study sites were net contributors to the suspended sediment load). The trapping factor is a robust metric for comparing three streams of varied watershed and geomorphic character, it promises to be a useful tool for future stream assessments. Published 2012. This article is a U.S. Government work and is in the public domain in the USA.